Modeling and numerical sensitivity study on the conjecture of a subglacial lake at Amundsenisen, Svalbard - Mansutti, Daniela; Bucchignani, Edoardo; Otero García, Jaime; Glowacki, Piotr (Applied Mathematical Modelling, 2015)
We present a new numerical procedure to assess the plausibility of a subglacial lake in case of relative small/moderate extension and surging temperate icefield. In addition to the flat signal from Ground Penetrating Radar remote survey of the area, early indication of a likely subglacial lake, required icefield data are: top surface elevation and bathymetry, top surface velocity at some points, in-depth temperature and density profiles of upper layer. The procedure is based on a mathematical model of the evolution of dynamics and thermo-dynamics of the icefield and of a subglacial lake. The Glen’s law is adopted for ice rheology and Stokes reduction is applied; Large Eddy Simulation technique is used for the lake. Ice/water phase change is described. Finite volumes for model discretization and a front-tracking technique to follow the moving interface characterize the numerical method. We have applied this procedure to the case of a subglacial lake conjectured in the area of Amundsenisen, Svalbard, and, here, the results of a sensitivity study are discussed. In particular we point out that the effect of firn and snow upper layers on the system, in terms of temperature field, density and water content, has to be included in the modeling, as it contributes to the overcoming of the ice metastable state and the release of subglacial water. Accordingly, ice water content changes have to be carefully described. The depth of the bed depression is confirmed to be critical for the formation of the lake.